(untitled) (Academic Journal of Internal Affairs, 2021)
For a long time, the most significant development project of the government’s HR policy after 2010 has been the project titled ’Strategic support for the supply of competitive public service personnel.’ The name of the project is a good expression for the focus of development, which is directed on increasing competitiveness and sustainable supply of personnel in the long run. Whatever it is, neither of them can be implemented without data- and fact-based workforce planning, so the development of an IT system supporting government personnel decisions is of high priority in the project. The aim of the study is to address the issue of optimal staff in national and international contexts, the importance of strategic workforce planning and its results abroad. Further goals are to analyze the attempts to establish a public service personnel register, together with its failures and lessons learned, and to present in details the IT system implemented within the framework of the project. The authors are convinced that the new personnel IT system will make Hungary to one of the leading countries in the field of both public service HRM and administrative digitalization.